2018
DOI: 10.1097/md.0000000000010928
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intensity-modulated radiotherapy vs 3-dimensional conformal radiotherapy for patients with non-metastatic esophageal squamous cell carcinoma receiving definitive concurrent chemoradiotherapy

Abstract: Whether the survival outcome of patients with non-metastatic esophageal squamous cell carcinoma (NM-ESCC) receiving definitive concurrent chemoradiotherapy (CCRT) is better with intensity-modulated radiotherapy (IMRT) or with 3-dimensional conformal radiotherapy (3DCRT) has been debated in the literature. We designed this population-based propensity-score (PS)-matched analysis to address this question. We identified eligible patients diagnosed between 2008 and 2015 from the Taiwan Cancer Registry and construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
11
3
Order By: Relevance
“…More than two-thirds of patients with hematological toxicity or gastrointestinal reaction received chemoradiotherapy. In this study, the incidence of radiation pneumonitis was lower than that shown in previous studies [25]. In addition, grade 1-2 radiation pneumonitis occurred in six (10.3%) and eight (11.9%) patients in the LD and HD groups, respectively, with controllable symptoms.…”
Section: Discussioncontrasting
confidence: 72%
“…More than two-thirds of patients with hematological toxicity or gastrointestinal reaction received chemoradiotherapy. In this study, the incidence of radiation pneumonitis was lower than that shown in previous studies [25]. In addition, grade 1-2 radiation pneumonitis occurred in six (10.3%) and eight (11.9%) patients in the LD and HD groups, respectively, with controllable symptoms.…”
Section: Discussioncontrasting
confidence: 72%
“…Hematological toxicity and gastrointestinal reactions were also common, and only hematologic toxicity was signi cant between the two groups. In this study, the incidence of radiation pneumonitis was lower than in previous studies [19]. Grade 1-2 radiation pneumonitis occurred in six (10.3%) and eight (11.9%) patients in the LD and HD groups, respectively, and the symptoms was controllable.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present report, grade 3 non-hematological or hematological toxicities were an infrequent occurrence; however, complete data on chronic toxicity was unavailable for a detailed analysis. Advances in delivery techniques have also led to further decrease in treatment related toxicities and reduced potential for marginal misses thereby improving both compliance and local control (6,29). Concurrent chemotherapy had a significant impact on DFS and OS on univariate analysis, but not on multivariate analysis, possible because of multi-collinearity with other unadjusted correlated variables.…”
Section: Discussionmentioning
confidence: 99%